PENERAPAN CASH MANAGEMENT SYSTEM SEBAGAI SISTEM BELANJA DI CABANG DINAS ENERGI DAN SUMBER DAYA MINERAL WILAYAH MERAPI - Rosalyni, Griselda Enika Noora; Khabibah, Nibras Anny (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2020)
Cash Management System is a service used to manage non-cash transactions using intermediaries. The purpose of this study is to determine how the application of Cash Management System or Non-Cash Transactions as a shopping system in Branch of Departement of Energy and Mineral Resources of Merapi Region. The method used in this research is descriptive qualitative method with primary data sources and secondary data. The result of this research is Cash Management System makes the payments easy, without cash withdrawals, only directly transferring the money to the third party.